The Effect of Coffee and Tea on Blood Pressure of University Students - Sumiya, Uyanga; Ni, Hanyin; Berger, Paul D. (Advances in Social Sciences Research Journal, 2019)
We collected data on blood pressure from randomly selected university students before and after they consumed a caffeinated beverage. The experiment was a two-level two-factor complete-factorial design with eight replicates. One factor is gender with Female and Male as the levels. The other factor is drink type with Coffee and Black Tea as the levels. There was no effect on the systolic blood pressure (SBP) and the diastolic blood pressure (DBP) due to the different caffeine drinks (coffee or black tea). Gender was a significant factor that affects the SBP and the DBP. The interaction effect of caffeinated drink and gender was not significant for either blood pressure measurement.